Paleoclimate support for a persistent dry island effect in the Colombian Andes during the last 4700 years. (February 2018) - Bird, Broxton W; Rudloff, Owen; Escobar, Jaime; Gilhooly, William P; Correa-Metrio, Alex; Vélez, Maria; Polissar, Pratigya J
We investigated middle- and late-Holocene hydroclimate patterns in the Colombian Andes using indicators of watershed erosion (lithic abundance), precipitation intensity (% silt), lake-level variability (organic carbon and nitrogen, % sand, and diatoms), and fire frequency (fossil charcoal) from a 4700-year-long sediment archive from Laguna de Ubaque, a small sub-alpine lake on the eastern flank of the eastern Colombian Andes. Our results indicate reduced precipitation, low lake levels, and increased fire occurrence at Ubaque between 4700 and 3500 cal. yr BP (hereafter BP). Precipitation and lake levels increased abruptly while fire occurrence decreased between 3500 and 2100 BP, with the exception of a 300-year dry phase between 2800 and 2500 BP. Although wetter than the 4700–3500 BP interval, precipitation decreased, lake levels fell, and fire occurrence increased after 2100 BP, but with high-frequency variability. Comparison of the Ubaque results with other Colombian paleoclimate records (e.g. Lakes Fúquene and La Cocha) supports an antiphase pattern of precipitation between the high/interior Andes and frontal slope sites. This spatial pattern of variability is consistent with modern responses to the changes in terrestrial atmospheric convection associated with the so-called 'dry island' effect. Further comparison with paleoclimate records from Venezuela suggests that the millennial trend toward increasing frontal slope precipitation is consistent with orbitally induced increases in Andean atmospheric convection. Sub-orbital dry island–like hydroclimate variability suggests that other mechanisms that affect Northern Hemisphere convection may act to enhance or diminish this effect on centennial and shorter timescales.